An Industry Study of Corporate Profits - Evans, Michael K. (Econometrica, 1968)
A corporate profits function is first developed in which gross profits depend positively on unlagged current dollar sales and capacity utilization rates and negatively on lagged sales. This function is tested for all two-digit manufacturing industries. It is found that the estimates differ substantially but similar results can be grouped into primarily competitive and primarily oligopolistic industries. Further testing with unit labor costs as an additional independent variable shows that competitive industries pass on increased labor costs in the form of higher prices much more readily than do oligopolistic industries. Finally, an aggregate econometric model is used to show that an overall increase in unit labor costs is reflected almost entirely in higher prices and decreases corporate profits very little. ALTHOUGH PROFITS are often considered to be one of the most important variables in our economic system, very little empirical analysis has been undertaken to establish the determinants of corporate profits, and even less work has been done at the two-digit industry level. This is somewhat surprising in view of the large amount of recent analysis of investment functions at the two-digit level and the often stated premise that investment depends partially on retained profits. Previous studies by Kuh2 and Schultze3 have been directed more toward an examination of the cyclical behavior of income shares rather than the determinants of profits per se. There is general agreement that these two aspects of profit behavior cannot be entirely separated, and it is argued later that one problem cannot be solved independently of the other. In this paper, however, we feel that it is preferable to specify a corporate profits function first and examine the relationship between profits and wages later. The purposes of this paper are threefold: (1) to determine a corporate profits function for two-digit industries; (2) to discuss and explain the interindustry similarities and differences; and (3) to show the relationships between profits and wages in the entire economy by use of a complete model. The model used for this purpose is one developed by the author and L.R. Klein, known as the WhartonEFU model.4 This is necessary in order to examine the redistribution of income through price changes and changes in the amount of labor demanded. In Section 1 ' The author is indebted to L. R. Klein and P. Davidson for numerous helpful suggestions and comments. M. Golubitsky was particularly helpful in writing the computer programs and performing most of the calculations for this paper. This is a project of the Econometric and Forecasting Unit of the